Dose-Response Analysis of Exposure to Arsenic in Drinking Water and Risk of Skin Lesions: A Systematic Review of the Literature - Paolo Boffetta; Carlotta Zunarelli; Claire Borron (Dose-Response, 2020)
Background: Exposure to high arsenic concentrations in drinking water has been associated with skin lesions. Our goal was to conduct a systematic review of studies on skin lesions and arsenic exposure, with emphasis on results at low level of exposure. Methods: We conducted a systematic review of studies reporting estimates of either prevalence or risk of skin lesions associated with exposure to more than 2 levels of arsenic in drinking water. We reviewed and abstracted the relevant results, with the aim of conducting a dose-response meta-analysis. Results: Nine studies of skin lesions were reviewed. Strong heterogeneity in the results did not meet the criteria for performing a meta-analysis. The relative risks for an increase of 10 μg/L arsenic in drinking water ranged from 1.002 to 1.140 (p-value of heterogeneity < 0.0001). Protection from bias and confounding was inadequate in most studies. Conclusion: Current studies are inadequate to conduct meta-analysis on dose-response relationship between exposure to arsenic in drinking water and skin lesions. Studies with complete exposure histories indicate skin lesions are associated with arsenic exposure in excess of 50 µg/L or higher.